2018
DOI: 10.1027/1016-9040/a000335
|View full text |Cite
|
Sign up to set email alerts
|

Identity Development in Immigrant Youth

Abstract: Abstract. Rates of immigration are at an all-time high in many Western countries, and immigration can exert profound influences on identity development. These influences occur both at the individual level and at the group level, but these two sets of influences have rarely been considered simultaneously. Accordingly, this article adopts a multilevel approach to identity development among immigrant youth, with a focus on North American receiving contexts. We focus not only on individual ethnic, national, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 94 publications
0
47
1
Order By: Relevance
“…Therefore, changes in one of these identity domains are expected to correlate with, or even precipitate changes in the other identity domains. Second, at least some aspects of personal identity may be assigned, informed, or constrained by ethnic or national group membership (Schwartz et al, 2018 ), or cultural orientation (Triandis, 2001 ). Thus, personal identity might be affected by national and ethnic identities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, changes in one of these identity domains are expected to correlate with, or even precipitate changes in the other identity domains. Second, at least some aspects of personal identity may be assigned, informed, or constrained by ethnic or national group membership (Schwartz et al, 2018 ), or cultural orientation (Triandis, 2001 ). Thus, personal identity might be affected by national and ethnic identities.…”
Section: Introductionmentioning
confidence: 99%
“…While ample research has examined the links between particular acculturation profiles of identification and measures of psychological and sociocultural adjustment, there is a lack of both empirical evidence and theorizing on how adolescents develop a particular acculturation profile of identification in the first place (c. Schwartz et al 2018 ). A rich literature on ethnic-racial identity, however, suggests that ethnic identity development starts already in childhood and continues into adulthood (Umaña-Taylor et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying more strongly with one’s ethnic group in response to ethnic discrimination has been termed reactive identification (Verkuyten 2018 ) or reactive ethnicity (Rumbaut 2008 ). It can be seen as a strategic reaction because it seems most fruitful to choose identity options that are actually available to oneself (Schwartz et al 2018 ). Past research confirmed that ethnic discrimination boosts ethnic identification (Skrobanek 2009 ) while decreasing national identification (Fleischmann et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of developing and examining broader theories is increasingly acknowledged and there are, for example, an increasing number of multilevel approaches in the study of immigrants’ identity development (Schwartz, Meca, Cano, Lorenzo‐Blanco, & Unger, ) and approaches focusing on person‐context congruency (e.g., Byrd & Chavous, ). In addition, there are attempts to integrate psychological approaches that focus more on the gradual development of an inner sense of a bicultural self (e.g., Benet‐Martínez & Haritatos, ; Syed & McLean, ) and social psychological approaches that tend to focus on contextual processes of dual group identifications (e.g., Hopkins, ).…”
Section: Implications For Future Researchmentioning
confidence: 99%